Numerical investigation on sealing performance of drainage pipeline inspection gauge crossing pipeline elbows - Jiang, Jinxu; Zhang, Hong; Ji, Beilei; Yi, Feining; Yan, Feng; Liu, Xiaoben (Energy science & engineering, 2021)
A pipeline inspection gauge (PIG) is routinely passed throughout the long‐distance oil and gas pipelines by pipeline operators to clean the pipeline. Sealing performance is a significant evaluation index for PIG's safety operation. To comprehensively evaluate the PIG's seal performance, nonlinear finite element models were developed, and parametric analysis was conducted in this study. The accuracy of simulation model was validated from numerical and experimental results reported in the literature. The results show that comparing with the pigging in straight pipes, the sealing rubber cups of PIGs can be more easily detached from the pipe wall when passing through elbows, causing smaller sealing areas. For a typical elbow (with curvature radius equals to six times of pipe diameter) widely used in pipeline industry, the minimum sealing area of rubber cup is only 8.07% during common operation conditions. The sealing ability of rubber cups can be obviously enhanced by increasing the curvature radius for the pigging operation of small curvature elbow. Elbow radius slightly affects the cup's sealing behavior when the curvature radius is over six times of pipe's outer diameter. An increment in sealing cup interference can increase the contact area between cup and pipe wall, and the blockage risk of PIGs will be reduced due to the good sealing ability and sufficient driving force. The minimum interference required for the cups is 4% under a most common operation condition; that is, the sealing cup thickness, fluid pressure difference, and friction coefficient are 35 mm, 0.02 MPa, and 0.3, respectively. A proper decrease in sealing cup thickness will reduce the stiffness of rubber cups, indicating that the cups with a smaller thickness are more prone to deformation. Thus, an increase in differential pressure over PIG can enhance the sealing performance of cups when the cups are separated from pipe wall. A large friction coefficient is risky for a safe pigging due to the decrease in sealing region with the increase in friction coefficient. In engineering practice, proper measures should be taken to reduce friction force. Above all, the results obtained in this study provide a reference for the structural design of PIGs. We investigated the sealing performance of drainage pipeline inspection gauge crossing pipeline elbows based on numerical simulation method. The two‐parameter Mooney‐Rivlin model was verified and utilized. Effects of common engineering parameters on PIG's sealing behavior were obtained through parametric analysis.